SAT0307 MRI changes in psoriatic arthritis in the first 12 weeks of anti TNF therapy: Comparison of high and low field images. (23rd January 2014) - Feletar, M.; Hall, S.; Bird, P.
Abstract : Background: Medications targeting TNF have definitively been shown to act as disease modifying therapy in Psoriatic arthritis (PsA), capable of improving symptoms (enthesitis, synovitis, tenosynovitis, dactylitis, ) and retard radiographic progression of erosions. Patients typically experience symptom relief within weeks of therapy intitiation Objectives: This study had 2 objectives: (i) compare the ability of 2 types of Magnetic Resonance Imaging (MRI) scans, low field (LF) (0.2 T Esaote), and high field (HF) (1.5T), to detect features of tendon and joint inflammation in active PsA at baseline and serially in the first 12 weeks of anti TNF therapy; (ii) to assess the relative ability and speed of TNF inhibition to reverse the MRI features of PsA. Methods: Patients with active PsA of hands or feet, meeting CASPAR [1] criteria, with a normal GFR and qualify for anti- TNF therapy as per the local medical guidelines, were eligible to be recruited. The choice of anti TNF therapy used was made by the treating clinician. Only the MRI reader (PB) was blinded to clinical data and therapy. Imaging studies were performed at 0, 2, 6 and 12 weeks where possible, requiring 2 MR scans at each time point, a high and low field, and Gadolinium enhancement administered with each HF and LF scan. Clinical data was recorded at 0 and 12 weeks. A standardised protocol for imaging was used. High field were studies read in sequence for all patients. Where LF studies were available, these were read in sequence one week after the HF studies. Studies were read once. The most affected digit was recorded during image interpretation. Results: Nine patients (pts) with active PSA were recruited. All had clinical evidence of dactylitis at baseline and had serial imaging of the most affected hand. Paired images including high and low field at each time point were available in 6 patients. Tenosynovitis (TS) was seen in 7/9 pts, better seen on HF than LF. Six of these demonstrated reduction in TS score on HF MRI at 2 weeks, 3 patients demonstrating marked improvement. Improvement at week 2 was also seen on LF imaging. Bone edema was identified on HF in 6/9, with complete resolution at 2 weeks in 4 of these pts. Synovitis was recorded in 8 pts in HF of which 6 improved at 2 weeks with further improvement through 12 weeks. Low field imaging demonstrated less sensitivity to synovitis and bone edema than high field imaging. These improvements were concordant with clinical findings. High field scores were more sensitive to the presence of disease features (tenosynovitis, bone oedema) and showed greater responsiveness to change Conclusions: TNF inhibitors rapidly reverse the MRI features of active psoriatic arthritis in the first 12 weeks of therapy, with improvement seen as early as 2 weeks. High field MRI demonstrated greater responsiveness to change compared with low field, especially for tenosynovitis. References: Taylor W, Gladman D, Helliwell P, et al; CASPAR Study Group. Classification criteria for psoriatic arthritis: development of new criteria from a large international study. Arthritis Rheum. 2006 Aug;54(8):2665-73. J Rheumatol. 2011 Sep;38(9):2034-8. The OMERACT Psoriatic Arthritis Magnetic Resonance Imaging Score (PsAMRIS) is reliable and sensitive to change: results from an OMERACT workshop. Bøyesen P, McQueen FM, Bird P et al Disclosure of Interest: M. Feletar Grant/Research support from: funded by Schering Plough, S. Hall Grant/Research support from: funded by Schering Plough, P. Bird Grant/Research support from: funded by Schering Plough